Lymphokine‐activated Killer Induction and Its Regulation by Macrophages in Malignant Pleural Effusions - Yanagawa, Hiroaki; Sone, Saburo; Nii, Akihiko; Fukuta, Katsuyuki; Nakanishi, Mie; Maeda, Ken‐ichi; Honda, Mitsuo; Ogura, Takeshi (Cancer science, 1989)
Mononuclear cells (MNC) from pleural effusions and peripheral blood of 18 patients with primary lung cancer with malignant pleural effusion were studied. Pleural and blood MNC generated lymphokine‐activated killer (LAK) activity similarly when cultured for 4 days with an optimal concentration of interleukin 2 (IL‐2). Highly purified lymphocytes (>98%) and monocyte‐macrophages (>90%) were isolated by discontinuous Percoll gradient centrifugation from pleural and blood MNC. Pleural macrophages, as well as blood monocytes, showed significant augmenting effects on in vitro LAK cell induction from pleural and blood lymphocytes by IL‐2. During daily intrapleural administration of IL‐2, significant induction of LAK activity in vivo was observed after 3 days, but then this LAK activity in pleural MNC decreased almost to zero by day 15. Daily injections of IL‐2 resulted in reduction in the up‐regulation of LAK induction by pleural macrophages and also in increase in the levels of soluble IL‐2 receptors in pleural effusions. These findings indicate that in vivo LAK induction of lymphocytes in malignant effusions by IL‐2 may be regulated by macrophages in the effusions.